Analisis Yuridis Pentingnya Pembuatan Perjanjian Perkawinan Berdasarkan Perspektif Hukum Perdata - Rastini; Jaka Bangkit Sanjaya; Rizqi Mulyani Slamet (Jurnal Hukum Lex Generalis, 2021)
The making of a marriage agreement is basically very necessary for prospective married couples who will hold a marriage, the marriage agreement deed is very useful and is also a form of self-protection. There are several divorces caused by wealth. Therefore, it is necessary to have a deed of marriage agreement in anticipation of problems that arise in the future. The writing of this paper aims to explain the flow of marriage agreement deed making and the urgency of making marriage agreement deeds for Indonesian citizens who perform mixed marriages with foreigners. The research method of this paper is juridical normative and uses a statutory approach.